A New Cardiac Channelopathy: From Clinical Phenotypes to Molecular Mechanisms Associated With Nav1.5 Gating Pores - Moreau, Adrien; Chahine, Mohamed (Frontiers in Cardiovascular Medicine, 2018)
Voltage gated sodium channels (NaV) are broadly expressed in the human body. They are responsible for the initiation of action potentials in excitable cells. They also underlie several physiological processes such as cognitive, sensitive, motor, and cardiac functions. The NaV1.5 channel is the main NaV expressed in the heart. A dysfunction of this channel is usually associated with the development of pure electrical disorders such as long QT syndrome, Brugada syndrome, sick sinus syndrome, atrial fibrillation, and cardiac conduction disorders. However, mutations of Nav1.5 have recently been linked to the development of an atypical clinical entity combining complex arrhythmias and dilated cardiomyopathy. Although several Nav1.5 mutations have been linked to dilated cardiomyopathy phenotypes, their pathogenic mechanisms remain to be elucidated. The gating pore may constitute a common biophysical defect for all NaV1.5 mutations located in the channel’s VSDs. The creation of such a gating pore may disrupt the ionic homeostasis of cardiomyocytes, affecting electrical signals, cell morphology, and cardiac myocyte function. The main objective of this article is to review the concept of gating pores and their role in structural heart diseases and to discuss potential pharmacological treatments.